2014
DOI: 10.4081/arc.2014.5459
|View full text |Cite
|
Sign up to set email alerts
|

A workshop for the king

Abstract: Through the use of single context planning, combined with archaeobotanical and dendrochronological investigations and extensive sampling for archaeometallurgical analysis, it was possible to reconstruct the use of the workshop at Viborg Søndersø in detail. The investigations were made in close cooperation between an archaeologist (Turi Thomsen), an archaeobotanist (Annine Moltsen), a dendrochronologist (Aiofe Daly) and an archaeometallurgist (the author), the last three now members of the <em>Danish Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Typologically, the metal artifacts are Germanic, and generally belong within the second to first centuries BC, with a few finds potentially extending into the first century AD. Metallurgical analyses indicate a local Jutish provenance ( 20 ). Two spearheads are dated to the sixth century AD, and may belong to a different event.…”
Section: Resultsmentioning
confidence: 99%
“…Typologically, the metal artifacts are Germanic, and generally belong within the second to first centuries BC, with a few finds potentially extending into the first century AD. Metallurgical analyses indicate a local Jutish provenance ( 20 ). Two spearheads are dated to the sixth century AD, and may belong to a different event.…”
Section: Resultsmentioning
confidence: 99%
“…A workshop in the late Viking Age settlement of Viborg Søndersø in Jutland (Denmark) offers the most detailed insight into the combination of such activities. Studies of its well-preserved microtopography showed evidence of varied use (Jouttijärvi et al, 2005; Jouttijärvi, 2014), including iron smithing, casting of silver, bronze, and lead, as well as comb-making, i.e. evidence of multiple crafts.…”
Section: Multi-crafters or Interdisciplinary Collaboratorsmentioning
confidence: 99%
“…Metallurgical analy-ses of the assemblage show that the bog iron probably derives from southern Sweden. An exception is the draw knife made of iron from Central Europe (Jouttijärvi 2017). All of the tools and ingots were made of high-quality steel by a skilled craftsman.…”
Section: Tools and Iron Hoardmentioning
confidence: 99%